2009
DOI: 10.1666/08-062.1
|View full text |Cite
|
Sign up to set email alerts
|

Cranial morphology and systematics of an extraordinary sample of the Late Neogene dwarf tapir,Tapirus polkensis(Olsen)

Abstract: The previously poorly known “Tapiravus” polkensis Olsen, 1960 (Mammalia, Perissodactyla, Tapiridae) is now known from abundant, well preserved specimens from both the type area in central Florida and from the Gray Fossil Site (GFS) in eastern Tennessee. The latter has produced over 75 individuals, the greatest number of tapirids from a single fossil site, including many articulated skeletons. Almost all linear measurements taken on skulls, mandibles, and cheek teeth from GFS have coefficients of variation less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 23 publications
(39 reference statements)
0
28
0
Order By: Relevance
“…In contrast, the morphometrics of the current T. bairdii seems to be more related with the North-American fossil tapirs (Ferrero and Noriega 2007) [T. johnsoni, T. simpsoni, T. polkenis and T. webbi for the Miocene; T. merriami, T. haysii from the Pliocene and these last two species plus T. veroensis for the Pleistocene; Hulbert 1995Hulbert , 1999Hulbert and Wallace 2005;Spassov and Ginsburg 1999;Tong 2005;Hulbert et al 2009]. This agrees quite well with the molecular data showed here, which showed T. bairdii as belonging to a different lineage.…”
Section: Temporal Splits Within T Pinchaque and T Bairdii Climaticmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, the morphometrics of the current T. bairdii seems to be more related with the North-American fossil tapirs (Ferrero and Noriega 2007) [T. johnsoni, T. simpsoni, T. polkenis and T. webbi for the Miocene; T. merriami, T. haysii from the Pliocene and these last two species plus T. veroensis for the Pleistocene; Hulbert 1995Hulbert , 1999Hulbert and Wallace 2005;Spassov and Ginsburg 1999;Tong 2005;Hulbert et al 2009]. This agrees quite well with the molecular data showed here, which showed T. bairdii as belonging to a different lineage.…”
Section: Temporal Splits Within T Pinchaque and T Bairdii Climaticmentioning
confidence: 93%
“…However, the discovery of 75 individuals of T. polkensis in the Gray Fossil Site in eastern Tennessee showed that a unique species was present but it had considerable intraspecific variation including development of the sagittal crest, outline shape of the nasals and the number and relative strength of lingual cusps on the P1 (Hulbert et al 2009). This means that some of the quoted fossils found in South-America should belong to T. terrestris.…”
Section: Temporal Splits Within T Pinchaque and T Bairdii Climaticmentioning
confidence: 99%
“…However, these studies often treat Tapirus either as a single morphological unit (e.g., Holbrook, ), or compare only one or two species of Tapirus with extinct tetradactyl perissodactyls (e.g., Radinsky, ; Simpson, ). Recent studies on the extinct tapirs of North America are beginning to increase species counts when performing comparative analyses, albeit with predominantly qualitative techniques (Holanda, Ribeiro, & Ferigolo, ; Hulbert, ; Hulbert et al, ). Using Tapirus as a solitary morphological unit is greatly beneficial for phylogenetic comparisons with more basal tapiromorph perissodactyls, for example, Lophiodon (Holbrook, ) and Colodon (Colbert, ), as it does not require exhaustive character comparisons across all species of tapir through time.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the 1st upper molar (M1) of tapirs erupts while the deciduous premolar dentition (dP2-dP4) is still in place. Specimens that retain dP2-dP4 are considered juveniles by most tapir taxonomists (e.g., Simpson 1945;Hulbert et al 2009;Hulbert 2010), who consider only specimens with erupted P4/p4 to be fully grown. Cozzuol et al (2013), however, mention neither premolar eruption nor any other ontogenetic criterion for sample membership in the context of their multivariate morphometric analysis.…”
Section: Multivariate Analyses Of Morphometric Datamentioning
confidence: 99%